A Conservative Treatment Approach to Replacing a Missing Anterior Tooth - Kunwarjeet Singh; Nidhi Gupta; Nandini Unnikrishnan; Vikram Kapoor; Dhruv Arora; Poonam K. Khinnavar (Hindawi Limited, 2014)
An implant-supported crown or conventionally fixed partial denture is the most common treatment modality to replace a missing anterior tooth but a more conservative approach, with a fiber reinforced composite resin FPD, can be used to replace a missing anterior tooth in young patients or when the patient does not agree for an implant, or conventional FPD or RPD therapy. It is an esthetic, conservative single sitting chairside procedure which can be used as a definitive treatment alternative in certain clinical situations for esthetic and functional replacement of a missing anterior tooth. To achieve desirable results, putty matrix was used for proper positioning of the pontic during direct fabrication of FRCFPD.